A review on risk mitigation of IT governance - Che Pa, Noraini; Anthony Jnr, Bokolo; Nor, Rozi Nor Haizan; Azmi Murad, Masrah Azrifah (Asian Network for Scientific Information, 2015)
Risk Mitigation (RM) is one of the important activities in risk management of IT governance. In IT governance project, IT risk mitigation emphasizes taking action early in a project to prevent the occurrence of undesired events or to reduce the consequences of their occurrence. The essential of RM in IT governance enables enterprise achieving "the new business changes, reduces IT project risks and future investment in IT governance projects. To get clear understanding in regards risk mitigation based on IT governance context, many relevant studies have been reviewed from different issues and aspects. The purpose of this study is to investigate related RM frameworks, models, processes, stakeholder involves and other issues based on a Systematic Literature Review (SLR) approach. This study presents the results of the systematic literature reviews on an evident of the RM in IT governance and it issues that need to be catered in the future. The finding of this review indicates that RM requires appropriate consideration to systematically reviewed on it numerous limitations, issues and current implementation.